Characterization of Fly ash and its Use in Sesamum on an Acid Soil - R.K. Nayak, D. Jena and M.R. Satpathy, K.K. Rout, A.K. Pal, Ipsita Das, Mitali Mandal (Journal of the Indian Society of Soil Science, 2016)
A field experiment was conducted on an acid soil to evaluate the effect of fly ash and paper mill sludge (PMS) on the growth, yield and quality of sesamum (Sesamum indicum) grown in kharif season under rainfed condition and on soil properties. Application of fly ash @ 40 t ha-1 along with 100% RDF significantly increased the seed yield over 100% RDF. However, highest yield of 10.3 q ha-1 was obtained with conjunctive use of fly ash and PMS applied @ 1 t ha-1 along with 100% RDF. But this is at par with the yield (9.4 q ha-1) obtained with 100% RDF + fly ash. Fly ash application did not have any significant effect on soil pH and concentration of Cd, Cr and Pb in post-harvest soil. The seeds in different treatments were also at par in terms of the concentration of these three heavy metals. Conjunctive use of fly ash and lime in acid soil proved better in terms of yield and soil health.